Symeon I Wielki w źródłach starobułgarskich X wieku (kilka uwag) - Leszka, Mirosław J. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The image of Simeon the Great in Bulgarian sources, both contemporary to his reign and written only a little later, seems rather one-sided and lacking significant details. The tsar is depicted as an outstanding, mighty monarch, deeply pious and well oriented in the Bible, as well as in the works of the patristic authorities (mainly Athanasius, Basil the Great and John Chrysostom), an avid reader and a lover of books. Simeon is thus a truly Christian ruler, a follower of peaceful policies, and a warrior only in the face of aggression. The foundations of his strength are supposed to lie in God’s protection. Such a depiction is far from the one preserved in the Byzantine literature, dominated by Simeon’s military activity. The paper is supplemented by the Polish translation of the Praise to Tsar Simeon (by Zofia Brzozowska) with the Old Church Slavonic original (post K. Kuev’s edition).